(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
The paper is designed and contextualized as a meaningful whole which includes the triple helix model: a combination of science, the real sector and local government. The basis of this research is teamwork in insurance companies operating in eastern Croatia whose indicators reflect on other insurance companies in Croatia and beyond. The conclusions of the paper suggest that teamwork is omnipresent in insurance companies, and that it affects the efficiency in meeting their objectives. A survey was used to test and prove the hypotheses, indicating that especially during the economic crisis it is crucial to invest in human resources and encourage teamwork via key motivational factors. The conclusions of the paper show that teamwork contributes to the efficiency of the organization, dissemination of new ideas and greater synergy within the insurance company. Keywords: Management, teamwork, efficiency, speed of changes, insurance